Strategy to Filter and Blocking Traffic Create by Anti-Censorship Software in Local Area Network - Kamal Harmoni, Kamal Ariff (2010)
Anti-censorship software originally develop to fight internet censorship in China. The anti-censorship software such as Ultrasurf, Freegate, Gpass, GTunnel and FirePhoenix are become popular for the user who used the internet for thier own's purpose and disobey the policies. Since it is widely use by users in organisation local area network to bypass firewall policies, it become a threat to LAN organization. Hence, it cause a problem for network administrator who manage the internet utilisation and enforcing internet policies. For an organisation, uncontrolled internet usage lead the opened system vulnerability to viruses, backdoor, non-productivity activities and slow internet connection. Thus, this studies proposed strategies to filter and blocking traffic create by anti-censorship software in LAN. Method used in this project is "design computer security experiment". Therefore, this project will guide the network administrator to control internet utilisation, protect organisation LAN and carried out implementation of the internal organization's internet policies.